Estimation of Site Amplifications from Shear-Wave Velocity at Pyroclastic Deposits and Basins in Aceh Tengah and Bener Meriah District, Aceh Province, Indonesia - Ibnu Rusydy; Khaizal Jamaluddin; Eldina Fatimah; Syafrizal Syafrizal; Fauzi Andika; Yoshinori Furumoto (TDMRC, Universitas Syiah Kuala, 2017)
Earthquake on July 2, 2013, destroyed several buildings in Aceh Tengah district and Bener Meriah district of Aceh Province. This earthquake gives Aceh government a clue that the seismic hazard map must become the reference in development plan in future. To respond this idea, we conduct the research and try to estimate the amplification factor for developing seismic hazard maps of those districts. This study aims to determine the average shear wave velocity up to the depth of 30 meters (Vs30) and the amplification factor of Aceh Tengah district and Bener Meriah district, to build the seismic hazard map of both districts. In this study, we use the MASW (Multi-Channel Analysis of Surface Waves) with 24 geophones in the frequency of 10 Hz at 10 locations to determine the Vs30 beneath the surface. The soil and rock classification from ASCE 2010 and SNI 1726:2012 used to classify the soil/rock based on Vs30 and calculate the predicted amplification factor using the Borcherdt Eeri equation. The result of this study reveals that the range of Vs30 in the study area is 76 m/s – 308 m/s. The loosest sediment has 76 m/s located at point 2 in Aceh Tengah district. The shear wave velocity of 76 m/s classifies as soft soil (SE). Based on the calculation, the pyroclastic deposit and sediment in the basin of the study area will be amplified the seismic wave in the range of 2.9 to 3.3 times. In the future, we suggest conducting another geophysical survey to determine the correct amplification factor to improve the quality of seismic hazard map.